Microbiological biostimulant promotes rooting of olive cuttings - Ritter, Giovana; Villa, Fabíola; da Silva, Daniel Fernandes; Alberton, Odair; Menegusso, Fernanda Jaqueline; Eberling, Tatiane; Dória, Joyce (International Journal of Agricultural and Biological Engineering, 2021)
The most widely used method of olive propagation is cutting, although for some cultivars the technique is still limited. The objective of this work was to evaluate the use of plant growth promoter bacteria and arbuscular mycorrhizal fungi in the rooting of olive cuttings. Two experiments were conducted from October 2017 to January 2018 with cuttings from 4 olive cultivars (Ascolano 315, Koroneiki, Maria da Fé and Picual) from four-year-old plants. The first experiment consisted of 4 olive cultivars and 3 mycorrhizal species plus the control and the second experiment of 3 concentrations of commercial inoculant (Nitro1000®), containing Azospirillum brasilense plus control. The cuttings were treated with 3000 mg/L of indolebutyric acid (IBA). The experimental design used in the two experiments was randomized blocks, in a 4 × 4 factorial scheme, containing 25 stakes per replicate and 3 replicates. The cuttings were kept under weaver conditions and within a low rooting tunnel. After 75 d, the percentage of rooted cuttings, callus and sprouts, length of the largest root, number and length of shoots were evaluated. The use of FMA in Maria da Fé and Picual has a positive response to cutting rooting and the fungi benefit the quality of the seedlings by the higher number of shoots and larger root length. The relation of Azospirillum brasilense cultivar is specific, being that, the cultivar Picual does not respond to inoculation of the bacterium having less viability in the propagation by cutting. Maria da Fé and Koroneiki have the best percentages of rooting with the use of 75.00 and 52.00 mL/L of inoculant, respectively. Keywords: Azospirillum brasilense, arbuscular mycorrhizal fungi, propagation, Olea europaea L., microorganism DOI: 10.25165/j.ijabe.20211406.5880 Citation: Ritter G, Villa F, da Silva D F, Alberton O, Menegusso F J, Eberling T, et al. Microbiological biostimulant promotes rooting of olive cuttings. Int J Agric & Biol Eng, 2021; 14(6): 207–212.